Relationship between shift work, night work, and subsequent dementia: A systematic evaluation and meta-analysis - Wang, Zhen-Zhi; Sun, Zhen; Zhang, Mei-Ling; Xiong, Kang; Zhou, Feng (Frontiers in Neurology, 2022)
Background The association between shift work, night work, and the risk of dementia are conflicting in the literature. Objectives This study was performed to obtain evidence on the potential relationship between shift work, night work, and dementia. Methods To investigate the link between shift work, night work, and dementia, we systematically searched PubMed, Embase, and Web of Science from inception to January 1, 2022. The eligibility of the retrieved records and extracted data were independently reviewed by two researchers. The Preferred Reporting Items for Systematic Evaluations and Meta-Analyses (PRISMA) statement was followed. STATA 16.0 was used to conduct the meta-analysis. Results A total of four studies involving 103,104 participants were included in this meta-analysis. Pooled results indicated that night shift workers had a 12% increased risk of dementia compared to subjects without night work (HR = 1.12, 95% CI 1.03–1.23, P = 0.094). Shift work was not significantly associated with dementia risk (HR: 1.09, 95% CI: 0.83–1.43, P = 0.546), but the effect of shift work on dementia risk appeared to increase with age, with a correlation observed among workers older than 50 years (HR = 1.31; 95% CI: 1.03–1.68, P = 0.030). Conclusion The data presented in our study suggest that night work may be a risk factor for dementia. More prospective studies with objective exposure measurements are required to further confirm this result. Systematic review registration https://doi.org/10.37766/inplasy2022.6.0079, identifier: INPLASY202260079.